Long-Term Exposure to AZT, but not d4T, Increases Endothelial Cell Oxidative Stress and Mitochondrial Dysfunction - Kline, Erik R. (2008)
Nucleoside reverse transcriptase inhibitors (NRTIs), such as zidovudine (AZT) and stavudine (d4T), cause toxicities to numerous tissues, including the liver and vasculature. While much is known about hepatic NRTI toxicity, the mechanism of toxicity in endothelial cells is incompletely understood. Human aortic endothelial and HepG2 liver cells were exposed to 1 μM AZT or d4T for up to 5 weeks. Markers of oxidative stress, mitochondrial function, NRTI phosphorylation, mitochondrial DNA (mtDNA) levels, and cytotoxicity were monitored over time. In endothelial cells, AZT significantly oxidized glutathione redox potential, increased total cellular and mitochondrial-specific superoxide, decreased mitochondrial membrane potential, increased lactate release, and caused cell death from weeks 3 through 5. Toxicity occurred in the absence of di- and tri-phosphorylated AZT and mtDNA depletion. These data show that oxidative stress and mitochondrial dysfunction in endothelial cells occur with a physiologically relevant concentration of AZT, and require long-term exposure to develop. In contrast, d4T did not induce endothelial oxidative stress, mitochondrial dysfunction, or cytotoxicity despite the presence of d4T-triphosphate. Both drugs depleted mtDNA in HepG2 cells without causing cell death. Endothelial cells are more susceptible to AZT-induced toxicity than HepG2 cells, and AZT caused greater endothelial dysfunction than d4T because of its pro-oxidative effects.